Imaging of cerebral blood flow markers in Huntington's disease using single photon emission computed tomography. - Reid, I C (1988)
Single photon emission computed tomography (SPECT) imaging of six Huntington's disease patients revealed a striking reduction in regional uptake of cerebral blood flow markers in vivo. Similar changes were found in one patient with "early stage" disease. The findings are compared with parallel magnetic resonance imaging (MRI) studies, and in one case, results of postmortem examination.